Pyrrolizidine alkaloids in bee pollen identified by LC-MS/MS analysis and colour parameters using multivariate class modeling. Issue 3 (March 2020) - De Jesus Inacio, Luciana; Merlanti, Roberta; Lucatello, Lorena; Bisutti, Vittoria; Contiero, Barbara; Serva, Lorenzo; Segato, Severino; Capolongo, Francesca
Abstract: Toxic pyrrolizidine alkaloids (PAs) and their N-oxides (PANOs) can be present in bee pollen depending on the plants visited by bees. A liquid chromatography-mass spectrometry (LC-MS/MS) method was developed and validated to monitor 17 PAs/PANOs in 44 bee pollens. The CIE-L ∗ a ∗ b ∗ colour coordinates with the specular component either included or excluded were recorded in pellets and ground aliquots. Lightness (L ∗ ) and yellowness (b ∗ ) of ground bee pollen were significantly correlated to PAs/PANOs content. The L ∗ and b ∗ cut-offs sorted by a receiver operating characteristic analysis to predict PAs/PANOs presence showed a significant increase in the relative risk to detect amounts higher than 84 μg kg −1 . Two supervised canonical discriminant analyses confirmed that pollen without PAs could be distinguished from those containing PAs/PANOs. The data suggest that instrumental colour coupled with supervised models could be used as a screening test for PAs/PANOs in bee pollen, before the confirmatory LC-MS/MS analysis. Abstract : Food Science; Food Safety; Public Health; Toxicology; Analytical Chemistry; Bee pollen; Pyrrolizidine Alkaloids; LC-MS/MS; CIE-L∗a∗b∗ colour coordinates; receiver operating characteristic; canonical discriminant analysis.